Impedimetric phosphorene field-effect transistors for rapid detection of lead ions. (5th July 2018) - Chang, Jingbo; Maity, Arnab; Pu, Haihui; Sui, Xiaoyu; Zhou, Guihua; Ren, Ren; Lu, Ganhua; Chen, Junhong
Abstract: Stimuli-responsive field-effect transistors (FETs) based on 2D nanomaterials have been considered as attractive candidates for sensing applications due to their rapid response, high sensitivity, and real-time monitoring capabilities. Here we report on an impedance spectroscopy technique for FET sensor applications with ultra-high sensitivity and good reproducibility. An alumina-gated FET, using an ultra-thin black phosphorus flake as the channel material, shows significantly improved stability and ultra-high sensitivity to lead ions in water. In addition, the phase angle in the low frequency region was found to change significantly in the presence of lead ion solutions, whereas it was almost unchanged in the high frequency region. The dominant sensing performance was found at low frequency phase spectrum around 50 Hz and a systematic change in the phase angle in different lead ion concentrations was found. Applying the impedance spectroscopy technique to insulator-gated FET sensors could open a new avenue for real-world sensor applications.